Ficus seedlings, subgenus Pharmacosycea (Moraceae), in Veracruz, Mexico - Ibarra-Manriquez, Guillermo (Instituto de Ecología, A.C., 1992)
The germination and morphology of seedlings of the following five species of Ficus subgenus Pharmacosycea, from Veracruz are described: Ficus insipida Willd., F. lapathifolia (Liebm.) Miq., F. maxima Mill., F. patenensis Lundell y F. yoponensis Desv. The five taxa have epigeal seedlings (phanerocotylar or Macaranga type). The germination in all species occurred within three weeks. The seedlings characteristics are very similar and do not permit the separation of species. The presence of hydathodes in the leaf margins is reported for the first time in the subgenus Pharmacosycea.